Predictors of in-hospital mortality in a cohort of people living with HIV (PLHIV) admitted to an academic medical intensive care unit from 2009 to 2014: A retrospective cohort study. Issue 28 (15th July 2022) - Sowah, Leonard A.; George, Nivya; Doll, Michelle; Chiou, Christine; Bhat, Pavan; Smith, Christopher; Palacio, Danica; Nieweld, Carl; Miller, Eric; Oni, Ibukunolupo; Okwesili, Christine; Mathur, Poonam; et al.
Abstract : Outcomes for critically ill people living with human immunodeficiency virus (PLHIV) have changed with the use of antiretroviral therapy (ART). To identify these outcomes and correlates of mortality in a contemporary critically ill cohort in an urban academic medical center in Baltimore, a city with a high burden of HIV, we conducted a retrospective cohort study of individuals admitted to a medical intensive care unit (MICU) at a tertiary care center between 2009 and 2014. PLHIV who were at least 18 years of age with an index MICU admission of ≥24 hours during the 5-year study period were included in this analysis. Data were obtained for participants from the time of MICU admission until hospital discharge and up to 180 days after MICU admission. Logistic regression was used to identify independent predictors of hospital mortality. Between June 2009 and June 2014, 318 PLHIV admitted to the MICU met inclusion criteria. Eighty-six percent of the patients were non-Hispanic Blacks. Poorly controlled HIV was very common with 70.2% of patients having a CD4 cell count <200 cells/mm 3 within 3 months prior to admission and only 34% of patients having an undetectable HIV viral load. Hospital mortality for the cohort was 17%. In a univariate model, mortality did not differ by demographic variables, CD4 cell count, HIV viral load, or ART use. Regression analysis adjusted by relevant covariates revealed that MICU patients admitted from the hospital ward were 6.4 times more likely to die in hospital than those admitted from emergency department. Other positive predictors were a diagnosis of end-stage liver disease, cardiac arrest, ventilator-dependent respiratory failure, vasopressor requirement, non-Hodgkin lymphoma, and symptomatic cytomegalovirus disease. In conclusion, in this critically ill cohort with HIV infection, most predictors of mortality were not directly related to HIV and were similar to those for the general population.